Remote Access Tools and DBMS for Modernising Research Libraries - V, Thangavel (Indonesian Journal of Library and Information Science, 2026)
Library services are being redefined by the incorporation of digital resources, which allow for innovation in everything from programming and collections to patron interaction and operational efficiency. Libraries' continued adoption of these technologies strengthens their position as forward-thinking, dynamic organisations, guaranteeing that their services continue to be significant and relevant in a quickly changing digital environment. This study, "Use of E-Resources by the Management Scholars and Faculty at the St. Francis Institute of Management and Research, Mumbai," suggests that remote access via academic libraries and library automation is a crucial component of educational institutions. The effect of remote access has transformed how libraries operate and their features, enabling them to perform more efficiently. Every piece of information that users come upon is something they want to peruse. They obtain their knowledge in a far-off location outside campus. The ideas, goals, and requirements of library automation are discussed in this article, along with the many add-ons that support library automation. Many software tools are available for automating tasks. This database management system for modernising Research libraries for remote access is followed using online libraries as access platforms, including Knimbus, Remotlog, MyLOFT, RemoteXS, EZproxy, Refread, and INFED. By creating user credentials and offering online education through various channels, consumers can now access subscribed resources remotely, utilising devices like laptops, cell phones, and personal computers, thanks to digital technology enabling this remote access by research libraries and their effective services for educational enrichment for the future generation